PNS dan Work From Anywhere: Implikasi Kebijakan Fleksibilitas Kerja di Sektor Publik - Ramadhan, Agung; Patricia, Anggun; Permata Sari, Novita; Putri, Rifa Aulya; Hanoselina, Yulia (Orasi: Jurnal Ilmu Politik dan Sosial, 2025)
Digital transformation and the experiences during the COVID-19 pandemic have driven significant changes in work patterns within the public sector, including the emergence of the Work From Anywhere (WFA) policy for Indonesia’s civil servants (ASN). This policy is viewed as having the potential to enhance efficiency, productivity, and service quality, although its implementation still faces various structural and cultural barriers. This study aims to analyze the implications of WFA adoption within ASN institutions by examining the factors influencing its effectiveness, its impact on employee performance and public service delivery, and lessons learned from international practices. The research employs a qualitative descriptive method, with data collected through a Structured Literature Review (SLR) based on systematic source selection using strict inclusion and exclusion criteria. The findings reveal that WFA offers several benefits, including increased productivity, time efficiency, improved work-life balance, and reduced operational costs. However, challenges remain, particularly regarding digital infrastructure disparities, technological literacy gaps, a work culture centered on physical presence, and weak performance-based evaluation systems. Lessons from other countries highlight the importance of digital leadership, trust-based organizational culture, and equitable infrastructure development. This study concludes that WFA has the potential to become a catalyst for digital bureaucratic reform, provided it is supported by clear regulations, enhanced ASN capacity, and a gradual and integrated transformation of work culture.